Experimental Study on Influence of Hardening of Isolator in Multiple Isolation Building - Fujita, Kohei; Miura, Toshiya; Tsuji, Masaaki; Takewaki, Izuru (Frontiers in Built Environment, 2016)
An innovative multiple isolation building system is proposed and the influence of hardening in seismic isolators on the response of a multiple isolation building is investigated by shaking table vibration tests for a scaled structural model. From the observation in recent earthquake disasters in far-fault ground motions, e.g. the 2011 off the Pacific coast of Tohoku earthquake, a significant concern is reminded that the long-period and long-duration ground excitation may cause severe damages to the existing base-isolated buildings. In order to enhance the seismic vibration suppression performance of those buildings, the multiple isolation structure has been developed recently as one of the innovative solutions. The multiple isolation structure is defined as a seismic isolated building which has multiple isolation stories by inserting supplemental isolators in the middle story in addition to the base. In this paper, the advantages of the proposed multiple isolation system subjected to an extremely strong far-field earthquake ground motion as the worst scenario are studied by the vibration test for a scaled model. In the scaled model, a non-linear restoring-force characteristic (hardening) is provided by the geometrical non-linearity which can be realized by inserting linear springs in the direction perpendicular to the vibration direction. The influence of this hardening property on the structural responses is studied by comparing with the responses of the same model without hardening effect. In the comparison with the base-isolated building, the fundamental seismic vibration suppression performances are evaluated in terms of the transfer functions of both a multiple isolation system and a base isolation system to the base input by sweeping frequencies of stationary sine waves using a controllable compact shaking table. In the numerical simulations, the effect of the friction in the isolation layers is also investigated.